T cells with low CD2 levels express reduced restriction factors and are preferentially infected in therapy naïve chronic HIV‐1 patients. Issue 1 (19th September 2017) - Bolduan, Sebastian; Koppensteiner, Herwig; Businger, Ramona; Rebensburg, Stephanie; Kunze, Christine; Brack‐Werner, Ruth; Draenert, Rika; Schindler, Michael
Abstract: Introduction : Restriction factors (RFs) suppress HIV‐1 in cell lines and primary cell models. Hence, RFs might be attractive targets for novel antiviral strategies, but their importance for virus control in vivo is controversial. Methods : We profiled the expression of RFs in primary blood‐derived mononuclear cells (PBMC) from therapy‐naïve HIV‐1 patients and quantified infection. Results : Overall, there was no correlation between individual RF expression and HIV‐1 status in total PBMC. However, we identified a T cell population with low levels of intracellular CD2 and reduced expression of SAMHD1, p21 and SerinC5. CD2 low T cells with reduced RF expression were markedly positive for HIV‐1 p24. In contrast, CD2+ T cells were less infected and expressed higher levels of RFs. CD2 low T cell infection correlated with viral loads and was associated with HIV‐1 disease progression. Conclusions : In untreated therapy naïve chronic HIV‐1 patients, RF expression in T cells is associated with CD2 expression and seems to influence viral loads. Our study suggests that RFs help to control HIV‐1 infection in certain T cells in vivo and supports the potential for RFs as promising targets for therapeutic intervention.